PENGGANTIAN BUNGKIL KEDELAI DENGAN PRODUK GELATINISASI CAMPURAN JAGUNG GILING-UREA DALAM RANSUM TERHADAP METABOLISME NITROGEN KAMBING KACANG (Replacement of soybean meal with gelatinized corn-urea mix in ration on nitrogen metabolism of kacang goats) - Edwin J. Lazarus; Emma D. Wie Lawa (Universitas Nusa Cendana, 2020)
The objective of this experiment was to evaluate replacement of soybean meal with corn mixed urea gelatinize product in concentrate as supplement of goats that supress nitrogen excretion and increase N metabolism. Sixteen Kacang goats (12.839±0.49 kg of live weight) were used in Completely randomized design with four treatments and four replication. The animals were randomly allocated to receive one of the following experiment diets Gliricidia + concentrate with ratio of soybean meal and product of gelatinize mixed corn-urea that: 1) 100:0 (P0), 2) 75:25 (P1), 3) 50:50 (P2) and 4) 25:75 (P3). Ration were formulated to contain 12% CP with ratio 60 % gliricidia and 40% concentrates. The result showed that total dry matter intake was significantly influenced of treatments and average of DMI each treatment was, P2 (467.99±2.19 g/h/d), P1 (441.20±2.10 g/h/d), P0 (440.08±2.29 g/h/d) and P3 (430.43±6.11 g/h/d). Dry matter and crude protein digestibility from each treatment was, P2 (76.45±0.39% and 80.63±0.37%), P1 (67.85±0.24% and 70.10±0.18%), P0 (67.85±0.74% and 70.68±0.42%) and P3 (60.62±0.41% and 61.96±0.69%). Treatment P2 highest than other treatments. Nitrogen retention and biological value significantly influenced of the treatment. Excretion of feces and urine lowest at P2 than P1, P0 and P3. N consumption, Total N Excretion and N digested not significantly influenced of the treatment but P2 better of other treatment. It could be concluded that 50% replacement soybean meal by product gelatinize of mixed corn-urea in concentrate has positive effects on nitrogen metabolism of Kacang goats.